The role of motivation in the disconnect between learned and applied spelling in written work with Grade 4 boys - Rimmer, Caroline (My University, 2022)
This doctoral thesis investigates the effect that motivation has on Grade 4 boys’ learned and applied spelling, and how the difficulties the boys’ experience influence their conscious choice of words when engaging with written tasks. The thesis has three conceptual bases: it draws on Piaget (1981) and Vygotsky (1978) to understand the different ways in which knowledge can be constructed. It draws on Gathercole and Alloway (2011), and Henry (2012) for a deeper understanding of the functioning of working memory. And it draws on the Unified Learning Model (ULM) (Shell et al, 2010), to position motivation within the learning process, and the effects motivation has on attention and working memory. Data was collected through interviews conducted with 18 Grade 4 boys. The boys were selected as a purposive sample: the researcher had given academic support to this group of boys for spelling and English the year before; the group is, academically, a mixed-ability group; 5 of the 18 boys had a clinical diagnosis of a learning impairment such as anxiety, ADD, ordyslexia an inability to process information quickly enough so as to make learning and recalling information easier; 5 boys were second language English users; all the boys in the group experienced difficulties with learning and applying spelling. The finding indicates that motivation, or the lack thereof, has a significant effect on the boys’ abilities to learn, conserve and apply their knowledge of spelling to written tasks. Because the boys do not have consolidated prior knowledge of spelling, the boys consciously choose simpler, easier-to-spell words when writing a creative paragraph where marks are deducted for spelling errors. The ULM offers a clearer understanding, on a neurobiological level, of the role motivation plays in these word choices.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Humanities, School of Education, University of the Witwatersrand, 2022